2018
DOI: 10.1080/19420862.2018.1452580
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and functional similarity of Amgen biosimilar ABP 215 to bevacizumab

Abstract: ABP 215 is a biosimilar product to bevacizumab. Bevacizumab acts by binding to vascular endothelial growth factor A, inhibiting endothelial cell proliferation and new blood vessel formation, thereby leading to tumor vasculature normalization. The ABP 215 analytical similarity assessment was designed to assess the structural and functional similarity of ABP 215 and bevacizumab sourced from both the United States (US) and the European Union (EU). Similarity assessment was also made between the US- and EU-sourced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 11 publications
2
65
0
1
Order By: Relevance
“…Covalent acetylation is also a possibility but lacks a plausible mechanism in the manufacturing and sample handling processes used and has not previously been observed for Avastin. Glycation has been proposed to occur in Avastin, however, we see no direct evidence for this phenomenon in the data (ie, it may account for some of the complexity in the peak distribution, but we cannot resolve individual peaks that would correspond to glycation). The next common glycosylation, G1F, involves the addition of a galactose to one of the N‐acetylglucosamine termini (Figure E).…”
Section: Resultsmentioning
confidence: 58%
“…Covalent acetylation is also a possibility but lacks a plausible mechanism in the manufacturing and sample handling processes used and has not previously been observed for Avastin. Glycation has been proposed to occur in Avastin, however, we see no direct evidence for this phenomenon in the data (ie, it may account for some of the complexity in the peak distribution, but we cannot resolve individual peaks that would correspond to glycation). The next common glycosylation, G1F, involves the addition of a galactose to one of the N‐acetylglucosamine termini (Figure E).…”
Section: Resultsmentioning
confidence: 58%
“…Similarity between ABP 215 and bevacizumab has been demonstrated in multiple, rigorous nonclinical and preclinical evaluations. ABP 215 has been shown to have the same primary and higher-order structure as bevacizumab (3). In addition, high similarity between ABP 215 and bevacizumab has been demonstrated with respect to biological functions in molecular studies and pharmacokinetic parameters in healthy volunteers (3,4).…”
Section: Introductionmentioning
confidence: 94%
“…ABP 215 has been shown to have the same primary and higher-order structure as bevacizumab (3). In addition, high similarity between ABP 215 and bevacizumab has been demonstrated with respect to biological functions in molecular studies and pharmacokinetic parameters in healthy volunteers (3,4). Here, we report the results of a phase III randomized study (MAPLE; registered at ClinicalTrials.gov, NCT01966003) comparing the efficacy, safety, immunogenicity, and pharmacokinetic profiles of ABP 215 and bevacizumab reference product (RP) in patients with advanced nonsquamous NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…All spectra exhibit strong β-sheet bands at around 1639 cm −1 and 1689 cm −1 as well as a β-turn band at around 1670 cm −1 , indicating the presence of antiparallel β-sheet structure typically observed in antibodies. 19 When compared with the reference spectrum of RS201505020304-RM04, the similarity of all samples were greater than 0.99. Collectively, DSC, CD and FTIR results demonstrated that the higher order structures of HLX01 were highly similar to those of the RPs.…”
Section: Resultsmentioning
confidence: 93%